Spatial and Temporal Variations of Cockle (Cerastoderma spp.) Populations in Two Portuguese Estuarine Systems With Low Directed Fishing Pressure - Santos, Cátia; Cabral, Sara; Carvalho, Frederico; Sousa, António; Goulding, Thomas; Ramajal, João; Medeiros, João Paulo; Silva, Gilda; Angélico, Maria Manuel; Gaspar, Miguel B.; Brito, Ana C.; Costa, José Lino; et al. (Frontiers in Marine Science, 2022)
Cockles are amongst the most exploited bivalve species in Portugal, playing an important ecological and socioeconomic role in coastal ecosystems. Two sympatric species of cockles, Cerastoderma edule (Linnaeus, 1758) and Cerastoderma glaucum (Bruguière, 1789) may co-occur in estuaries and coastal lagoons in mixed populations, along the European Atlantic coast, namely in Portugal, France and UK. The increasing importance of shellfish harvesting in Portugal requires a greater knowledge of cockle stocks and temporal variability to better inform sustainable management practices. Therefore, this study aimed at assessing inter-annual variations in cockles’ populations in two Portuguese estuarine systems where the species are exploited. Sampling was carried out using a clam dredge, covering the cockles’ entire potential area of occurrence at Tagus and Sado estuaries in three different years (2015, 2018 and 2019). Their abundance, spatial distribution and population structure were examined at each system. Moreover, several water and sediment parameters were measured, respectively, to understand the influence of environmental conditions on the spatial distribution and abundance of cockles. The results obtained showed that cockles occur mostly in the intermediate areas of both estuarine systems and are more abundant in the Tagus estuary. Estuary, depth, and average sediment grain size were the environmental factors that better explained the probability of species occurrence, showing that inherent characteristics of the two nearby estuarine systems influence the abundances of these bivalves. The population structure analysis indicated that natural and/or fishing mortality is constraining the cockles’ populations given the low abundance of adult individuals with marketable size in both estuaries. This study highlights the need for appropriate management measures to ensure the sustainability of these bivalve population stocks that have significant socioeconomic importance for local populations.